Diabetes in the classroom: a report on an educational activity with children - Partelli, Adriana Nunes; Brito Borges , Jennifer; Lopes Caetano , Ester; Ribeiro Souza, Kaylane; Freitas Santana , Yasmin; Pinheiro Lopes e Sousa , Igo (Guará Journal, 2025)
The objective was to discuss the process of developing, implementing, and evaluating the health education program entitled "Diabetes in the Classroom: An Experience Report in Health Education," developed with elementary school children, focusing on diabetes prevention and the promotion of healthy lifestyle habits in the school context. This is an experience report of an educational action developed by nursing students from a public university in the interior of Espírito Santo, in the second semester of 2025. The action was developed based on a situational diagnosis carried out in the Aviação neighborhood, where diabetes mellitus was identified as one of the most prevalent chronic conditions in the community. The process of constructing the educational proposal was conducted in four stages: planning, development of a product to assist in the action, implementation, and evaluation of the educational action. The main findings included high interest, active participation, and good assimilation of the content, favoring reflections on healthy eating and diabetes prevention. The experience highlights the relevance of nursing in promoting health in the school context and shows that playful educational strategies contribute to the development of self-care and the formation of healthy habits from childhood.